2022
DOI: 10.1101/2022.10.07.511315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predation, community asynchrony, and metacommunity stability in cyanobacterial mats

Abstract: Holistically characterizing mechanisms that connect biotic context with patterns in persistence across levels of ecological organization requires integrating patterns of variability across scale. This is especially true in microbial communities, where relevant trophic interactions operate across disparate spatiotemporal scales. Here, we integrated observational, experimental, and theoretical approaches to unify local and regional ecological processes driving the dynamics of benthic cyanobacterial mats on coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 147 publications
1
13
0
Order By: Relevance
“…Emerging evidence from examination of the nutritional ecology of nominal herbivores, specifically reef parrotfishes, suggests a fundamental preference for targeting cyanobacteria as nutritional resources by these fishes (Clements et al, 2017;Nicholson & Clements, 2020. Alongside this evidence from nutritional ecology, multiple observational studies now have confirmed the consumption of benthic cyanobacterial mats by multiple nominally herbivorous fishes on Caribbean reefs (Cissell et al, 2019;Cissell & McCoy, 2022b), including the documented preferential consumption by several of these fishes (Manning & McCoy, 2023). These various lines of evidence imply that the expansion of conspicuous benthic cyanobacterial assemblages may not inherently disrupt trophic flow through ecosystems (here, on coral reefs) owing to a lack of palatability as previously generally theorized (Ullah et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Emerging evidence from examination of the nutritional ecology of nominal herbivores, specifically reef parrotfishes, suggests a fundamental preference for targeting cyanobacteria as nutritional resources by these fishes (Clements et al, 2017;Nicholson & Clements, 2020. Alongside this evidence from nutritional ecology, multiple observational studies now have confirmed the consumption of benthic cyanobacterial mats by multiple nominally herbivorous fishes on Caribbean reefs (Cissell et al, 2019;Cissell & McCoy, 2022b), including the documented preferential consumption by several of these fishes (Manning & McCoy, 2023). These various lines of evidence imply that the expansion of conspicuous benthic cyanobacterial assemblages may not inherently disrupt trophic flow through ecosystems (here, on coral reefs) owing to a lack of palatability as previously generally theorized (Ullah et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Strong lineage‐specific patterns in intra‐mat trophic structure (Figures 4 and S16; potentially coupled to host trophic affiliation; Cissell & McCoy, 2022a; Cissell & McCoy, 2022b) may, in part, contribute to patterns of spatial genomic diversification among mat‐building populations and likely impact intra‐mat chemistry and nutrient recycling (Weitz & Wilhelm, 2012). Bacteria‐phage coevolution is known to increase both phage and bacterial divergence rates mediated via reciprocal adaptation (evolutionary conflict) and promote diversity across multiple levels of ecological organisation, affecting overall community structure (Koskella & Brockhurst, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic cyanobacterial mats (BCMs) are becoming increasingly dominant members of coral reef communities worldwide due to the influence of both local and global stressors (Cissell & McCoy, 2022a; de Bakker et al, 2017; Ford et al, 2018). We define coral reef BCMs as a functional grouping that broadly encompasses taxonomically and functionally rich, conspicuous benthic consortia primarily comprised of prokaryotic members of the phyla Cyanobacteria (dominating the construction and maintenance of mat structural complexity), Proteobacteria, and Bacteroidetes (Cissell & McCoy, 2021; Stuij et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Previous work on coral reef BCMs has focused on mat formation and growth, emphasizing the importance of bottom‐up and physical drivers in the proliferation of mat cover (Brocke et al, 2015; Kuffner & Paul, 2001). Past research on mat dynamics is also generally scale restricted and often focuses on reef sites (total benthic cover of BCMs) rather than documenting the dynamics of the individual component mat communities (but see Cissell & McCoy, 2022a). Conversely, limited attention has been given to understanding the natural senescence dynamics of mature BCM communities or elucidating the drivers and manifestations of individual mat physical trajectory and mortality.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation